A role for 5-HT in the action of antidepressant drugs. - Cowen, P (1990)
Administration of antidepressant drugs to rodents appears to decrease 5-HT2 receptor function while transmission through postsynaptic 5-HT1 receptor synapses may be enhanced. Antidepressant drugs also alter 5-HT mechanisms in humans; some of these changes are congruent with effects noted in animal studies. Thus certain 5-HT-mediated neuroendocrine responses are enhanced by tricyclic antidepressants and monoamine oxidase inhibitors, and it seems likely that tricyclics may act as 5-HT2 receptor antagonists in the human brain. However, there is presently no firm evidence that any of these changes are necessary for the clinical efficacy of antidepressant drugs. The best evidence that 5-HT neurons may be involved in mediating antidepressant effects is the antidepressant activity of selective 5-HT uptake blockers.